Anatomy of a genocide : the life and death of a town called Buczacz - Barṭov, ʾOmer 1954- (Simon & Schuster Paperbacks, 2019)
Chapter 1: The gathering storm -- Chapter 2: Enemies at their pleasure -- Chapter 3: Together and apart -- Chapter 4: Soviet power -- Chapter 5: German order --Chapter 6: The daily life of genocide -- Chapter 7: Neighbors